Evaluation on the potential of hot spring as nature tourism attraction in Lojing Highlands, Kelantan, Peninsula Malaysia - Saikim, Fiffy Hasnidah; Godoong, Elia; Hassin, Nor Hizami; Hamzah, Zulhazman; Mohd Nordin, Nordiana; Abdul Aziz, Nor Akmar (IOP Publishing, 2021)
Natural hot springs are a common occurrence in Malaysia. These natural hot springs occur when water seeps into the earth and is heated by magma and pressure causes the water to rise again as a heated pool or hot springs. Some locals believe that these natural hot springs have curative effects and can cure skin ailments such as rashes, pimples and fungi infections. Whether this is true or not remains to be scientifically proven, but these places have become a magnet for tourists and those seeking healing. Some of Malaysia's natural hot springs have developed into modern tourists' attractions with shops, rest houses, restaurants and changing rooms built nearby to accommodate visitors who are interested by this natural phenomenon and the best example is the Poring Hot Springs, in Ranau, Sabah. Consequently, the objective of this paper is to briefly highlight the potential of Lojing's hot springs as nature tourism attraction for the state of Kelantan. This paper provides a broad insight into the demand for services and facilities, location and characteristics of Lojing's geothermal and natural mineral water resources, the opportunities available to expand and establish new facilities and an indication of the success of Sabah's developments with the potential to be replicated in Lojing. Based on the content analysis done using Leximancer, it is apparent that Lojing's hot spring requires intervention in terms of strategies that aimed at increasing tourist satisfaction. It is suggested that the theme "leisure" to be concentrated as the pull factor for Lojing hot spring-based tourism.